Received Pronunciation as socio-linguistic and historical category - Жук, Валентина Аркадіївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
In this article the author defines standard as a linguistic, historical and social category, characterized by dynamism and stability. The article proves that by a person’s speech one can form an opinion as to where this person is from and which social class he (she) belongs to. It is shown that language situation in the UK is characterized by diglossia, under which there is a functional differentiation of different pronunciation types. The way basic communicative functions of RP (Received pronunciation) are distributed is pointed out.